FORMULATION EVALUATION AND OPTIMIZATION OF IMMEDIATE RELEASE TABLET OF ACECLOFENAC BY DIRECT COMPRESSION METHOD - Hazarika, Jahan Nur Rahman; Deb, Pulak (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of present work is to formulate and evaluate immediate release tablets of aceclofenac. Aceclofenac is effectively acting as non-steroidal anti-inflammatory drug (NSAID) of the phenylacetic acid group, which has properties such as anti-inflammatory, analgesic and antipyretic when given orally. Methods: First Pre-formulation studies were carried out such as FTIR, solubility, bulk and tapped density, hounars ratio, Carr's index, the angle of repose etc. Then the tablets were prepared by direct compression using super disintegrating agents (sodium starch glycolate). To obtain the desired optimum formulation several formulations had been performed with different excipients and their ration. For each formulation, post formulation parameters are determined including hardness, weight variation, friability, disintegration and in vitro dissolution, wetting time, water absorption ratio etc. Results: From the test performed it is found that the formulation F8 is best and satisfies all the criteria as immediate release tablet. Conclusion: From the result, it can be concluded that using Sodium Starch Glycolate at 4% will give the best in vitro drug release.